Maternal Characteristics and Histopathological Features of Placenta Accreta Spectrum in Dr. Hasan Sadikin General Hospital Bandung, Period 2015–2020 - Yuktiana Kharisma; Hasrayati Agustina; Sri Suryanti; Birgitta Maria Dewayani; Bethy Suryawati Hernowo (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The placenta accreta spectrum (PAS) incidence has inclined today. The PAS is divided into three histopathological classifications, including accreta, increta, and percreta, associated with maternal, fetal morbidity, and mortality. This study aimed to explore the maternal characteristics and histopathological features in PAS at Dr. Hasan Sadikin General Hospital Bandung.Methods: This descriptive observational study involved 135 cases from January 2015–December 2020 at Dr. Hasan Sadikin General Hospital that met the inclusion criteria. The PAS histopathological classification was evaluated based on maternal characteristics such as age, parity, cesarean section (CS), and miscarriage. Results: The incidence of placenta accreta from 2015 to 2020 was 37.0%, whereas increta was 43.4%, followed by percreta at 19.3%. The maternal age of placenta accreta and increta mainly occurred at the age of 30–34 years with the prevalence of 40% and 46%, respectively, whereas percreta was aged 35–39 yo (27%). Most parities in placenta accreta, increta, percreta were three. Interestingly, 93% of cases had a CS history. Furthermore, the miscarriage history for accreta was 18%, increta 29% and percreta 38%. Conclusion: The highest incidence of PAS in Dr. Hasan Sadikin General Hospital is placenta increta, which mainly occurs at the age of 30–34 years. Almost all PAS patients have a history of CS; however, most of the patients do not have a miscarriage history.